Hemostatic changes in patients with chronic renal failure - Serrheed, Harith Y.; Mohammed, Eman J. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Renal disease results in significant disorder of hemostasis (bleeding diathesis orhypercoagulable state).Objectives: This study is to determine the changes in some hemostasis parameters in patients withchronic renal failure and identify the effect of dialysis on these changes.Patients and Methods: seventy five patients with end stage chronic renal failure were collected fromBaghdad hospital, a full detailed history and clinical examination were performed, 50 patients were onmaintenance weekly hemodialysis, and 25 patients were without dialysis.Result: Bleeding time was significantly higher in patients with chronic renal failure who didn’t needany type of dialysis, positive D-Dimer test. In some patients, Platelet count, prothrombin time, thrombintime, fibrinogene level, activated partial thromboplastin time; all did not reach significant level betweenboth groups of patients.Conclusion: hemostatic changes are not uncommon in patients with chronic renal failure, affecting thedifferent parameter hemostasis so it should be consider in the management of these patients.